Burden of Illness in Adults With Hypophosphatasia: Data From the Global Hypophosphatasia Patient Registry. (10th August 2020) - Seefried, Lothar; Dahir, Kathryn; Petryk, Anna; Högler, Wolfgang; Linglart, Agnès; Martos‐Moreno, Gabriel Ángel; Ozono, Keiichi; Fang, Shona; Rockman‐Greenberg, Cheryl; Kishnani, Priya S
ABSTRACT: Hypophosphatasia (HPP) is a rare, inherited, metabolic disease caused by deficient tissue non‐specific alkaline phosphatase activity. This study aims to assess patient‐reported pain, disability and health‐related quality of life (HRQoL) in a real‐world cohort of adults with HPP who were not receiving asfotase alfa during the analysis. Adults (≥18 years old) with HPP (confirmed by ALPL gene mutation and/or low serum alkaline phosphatase activity for age/sex) were identified from the Global HPP Registry (NCT02306720). Demographics, clinical characteristics, and data on patient‐reported pain, disability, and HRQoL (assessed by Brief Pain Inventory Short Form [BPI‐SF], Health Assessment Questionnaire Disability Index [HAQ‐DI], and 36‐Item Short‐Form Health Survey version 2 [SF‐36v2], respectively) were stratified by pediatric‐ and adult‐onset HPP and summarized descriptively. Of the 304 adults included (median [min, max] age 48.6 [18.8, 79.8] years; 74% women), 45% had adult‐onset HPP and 33% had pediatric‐onset HPP (unknown age of onset, 22%). Of those with data, 38% had experienced ≥5 HPP manifestations and 62% had a history of ≥1 fracture/pseudofracture. Median (Q1, Q3) BPI‐SF scores were 3.5 (1.5, 5.3) for pain severity and 3.3 (0.9, 6.2) for pain interference. Median (Q1, Q3) disability on the HAQ‐DI was 0.3 (0.0, 0.7). Median (Q1, Q3) physical and mental component summary scores on the SF‐36v2 were 42.4 (32.7, 49.9) and 45.3 (36.3, 54.8), respectively. Greater numbers of HPP manifestations experienced/body systems affected correlated significantly with poorer scores on the BPI‐SF, HAQ‐DI, and SF‐36v2 (all p < 0.05). No significant differences between adults with pediatric‐ and adult‐onset HPP were observed for patient‐reported outcomes, except for disability and the BPI‐SF question "pain at its worst, " which were significantly higher among adults with pediatric‐ versus adult‐onset HPP ( p = 0.03 and 0.04, respectively). These data from the Global HPP Registry show that adults with HPP have a substantial burden of illness that is associated with reduced patient‐reported HRQoL, regardless of age of disease onset. © 2020 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).